A synonymous mutation in PI4KA impacts the transcription and translation process of gene expression - Zhang, Kaihui; Kang, Lili; Zhang, Haozheng; Bai, Lu; Pang, Huanping; Liu, Qinghua; Zhang, Xinyi; Chen, Dong; Yu, Haihua; Lv, Yuqiang; Gao, Min; Liu, Yi; et al. (Frontiers in Immunology, 2022)
Phosphatidylinositol-4-kinase alpha (PI4KIIIα), encoded by the PI4KA gene, can synthesize phosphatidylinositol-4-phosphate (PI-4-P), which serves as a specific membrane marker and is instrumental in signal transduction. PI4KA mutations can cause autosomal recessive diseases involving neurological, intestinal, and immunological conditions (OMIM:619621, 616531, 619708). We detected sepsis, severe diarrhea, and decreased immunoglobulin levels in one neonate. Two novel compound heterozygous mutations, c.5846T>C (p.Leu1949Pro) and c.3453C>T (p.Gly1151=), were identified in the neonate from the father and the mother, respectively. Sanger sequencing and reverse transcription polymerase chain reaction (RT-PCR) for peripheral blood and minigene splicing assays showed a deletion of five bases (GTGAG) with the c.3453C>T variant at the mRNA level, which could result in a truncated protein (p.Gly1151GlyfsTer17). The missense mutation c.5846T>C (p.Leu1949Pro) kinase activity was measured, and little or no catalytic activity was detected. According to the clinical characteristics and gene mutations with functional verification, our pediatricians diagnosed the child with a combined immunodeficiency and intestinal disorder close to gastrointestinal defects and immunodeficiency syndrome 2 (GIDID2; OMIM: 619708). Medicines such as immunomodulators are prescribed to balance immune dysregulation. This study is the first report of a synonymous mutation in the PI4KA gene that influences alternative splicing. Our findings expand the mutation spectrum leading to PI4KIIIa deficiency-related diseases and provide exact information for genetic counseling.